Budaya dan Pembangunan: Analisis Komunikasi Ritual Adat Erau di Kutai Kartanegara - Hairunnisa, Hairunnisa; Hanief, Lalita; Firliandoko, Robby; Rahmawati, Yulia; Wahyuningrum, Marliana (Universitas 17 Agustus 1945 Samarinda, 2026)
This research explores the role of ritual communication in the preservation of cultural identity and its relevance to sustainable development through the Erau Tradition in Kutai Kartanegara, East Kalimantan. Ritual communication as a form of symbolic communication emphasizes participation, repetition, and transmission of shared meanings within the community, not just linear transmission of information. Erau Tradition, a traditional ceremony originating from the Kutai Sultanate, exemplifies ritual communication through a series of ceremonies, dances, music, and symbolic actions. This research examines how these rituals help strengthen social cohesion, preserve cultural values, and maintain a spiritual connection with nature, with a focus on the messages conveyed regarding environmental conservation and community solidarity. This research highlights that Erau Tradition is not just a cultural celebration, but also a powerful tool for sustainable development. By integrating cultural heritage, social unity, economic empowerment and environmental awareness, the ritual contributes to a holistic approach to development. In addition, the Erau festival is a major attraction for cultural tourism that supports local economic growth while promoting cultural sustainability. This research argues that ritual communication in Erau Tradition can play a significant role in fostering inclusive and sustainable development, strengthening local identity, and increasing environmental awarenessPenelitian ini mengeksplorasi peran komunikasi ritual dalam pelestarian identitas budaya dan relevansinya terhadap pembangunan berkelanjutan melalui Adat Erau di Kutai Kartanegara, Kalimantan Timur. Komunikasi ritual sebagai bentuk komunikasi simbolik menekankan partisipasi, pengulangan, dan transmisi makna bersama dalam komunitas, bukan hanya transmisi informasi secara linear. Adat Erau, sebuah upacara tradisional yang berasal dari Kesultanan Kutai, menjadi contoh komunikasi ritual melalui rangkaian upacara, tarian, musik, dan tindakan simbolik. Penelitian ini mengkaji bagaimana ritual-ritual ini membantu memperkuat kohesi sosial, melestarikan nilai-nilai budaya, dan menjaga hubungan spiritual dengan alam, dengan fokus pada pesan-pesan yang disampaikan terkait pelestarian lingkungan dan solidaritas komunitas. Penelitian ini menyoroti Adat Erau bukan hanya perayaan budaya saja, tetapi juga merupakan alat yang kuat untuk pembangunan berkelanjutan. Dengan mengintegrasikan warisan budaya, kesatuan sosial, pemberdayaan ekonomi, dan kesadaran lingkungan, ritual ini memberikan kontribusi pada pendekatan pembangunan yang holistik. Selain itu, festival Erau menjadi daya tarik utama pariwisata budaya yang mendukung pertumbuhan ekonomi lokal sekaligus mempromosikan keberlanjutan budaya. Penelitian ini berargumen bahwa komunikasi ritual dalam Adat Erau dapat memainkan peran signifikan dalam mendorong pembangunan yang inklusif dan berkelanjutan, memperkuat identitas lokal, dan meningkatkan kesadaran lingkungan.